The Effectiveness of Gambir Leaves (Uncaria gambir roxb) as A Biocoagulant in Reducing Pollutant in Palm Oil Mill Effluent - Massaid, Andre; Putra, Syawal Andika; Anandhito, Muhammad Varrel; Habibullah, Ahmad Zaki; Maharjan, Namita; Putra, Alqadri Asri (LPPM Universitas Andalas, 2024)
Crude Palm Oil (CPO) production increased to 46.82 tons in 2022 (BPS), and this manufacturing process produces wastewaste that is harmful to the environment. The quality standards for palm oil mill effluent (POME) include BOD 100 mg/L, COD 350 mg/L, TSS 250 mg/L, oil and grease 25 mg/L, and total nitrogen 50 mg/L. POME with high organic content can cause eutrophication, siltation, and death of aquatic organisms. One method of treating this wastewater can be carried out through coagulation. In water treatment, chemical coagulants are typically used to remove impurities, but biocoagulants from Gambir leaves offer a natural and environmentally friendly alternative. These biocoagulants can effectively treat water while reducing the need for synthetic chemicals, presenting a sustainable solution. Gambir leaves contain polyphenolic compounds that are effective as biocoagulants. This study examines the effectiveness of Gambir leaves as a biocoagulant in reducing palm oil effluent pollutants, including TSS, BOD, COD, oil and grease, and total nitrogen. This study includes the initial steps in making biocoaglant until examining POME wastewater. Based on the results of the study, it was found that Gambir leaves extract has the potential to reduce pH and remove TSS, BOD, COD, oil and grease, and total nitrogen contained in POME with a concentration variation of 1000 mg/L, 2000 mg/L, 3000 mg/L, and 4000 mg/L.